1997
DOI: 10.1902/jop.1997.68.12.1215
|View full text |Cite
|
Sign up to set email alerts
|

Scanning Electron Microscopic Evaluation of the Effects of an Air‐Abrasive System on Dental Implants: A Comparative In Vitro Study Between Machined and Plasma‐Sprayed Titanium Surfaces

Abstract: An in vitro comparative study was conducted in order to evaluate the effects of an air-abrasive system on dental implant surfaces. Eight new titanium dental implants, four standard machined implants (machined group), and four standard plasma-sprayed implants (plasma-sprayed group) were selected for investigation. Both neck and body surfaces of the implants were analyzed. Each pair of implants in each group was treated as follows: the spray of the air-abrasive unit was applied to each area for 5 seconds on the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 14 publications
(8 reference statements)
0
27
2
Order By: Relevance
“…This finding is consistent with the study of Chairay et al, which found that one 15 second application of the same powder resulted in the same type of surface pitting effect. 164 In the present investigation, surface changes with sodium bicarbonate was seen in a shorter time frame than the 40-60 seconds reported by Kreisler and Schwarz for discs contaminated with biofilm. 81,93 The application of glycine powder did not cause observable effects on any of the three surfaces used.…”
Section: Sla Surfacecontrasting
confidence: 43%
See 2 more Smart Citations
“…This finding is consistent with the study of Chairay et al, which found that one 15 second application of the same powder resulted in the same type of surface pitting effect. 164 In the present investigation, surface changes with sodium bicarbonate was seen in a shorter time frame than the 40-60 seconds reported by Kreisler and Schwarz for discs contaminated with biofilm. 81,93 The application of glycine powder did not cause observable effects on any of the three surfaces used.…”
Section: Sla Surfacecontrasting
confidence: 43%
“…48,55,77 From a profilometry perspective, air polishing of an SLA surface does not alter or increase the original surface roughness. [162][163][164] From an SEM perspective, air polishing with sodium bicarbonate powder causes rounding of microscopic sharp edges, but does not cause pitting or other gross modifications after 5 seconds, however surface changes can be seen after 15 seconds with the same powder when applied at 52 PSI onto plasma sprayed or smooth surface implants. 164 The extent of surface damage is influenced strongly by the choice of abrasive powder, 55 with sodium bicarbonate and aluminium oxide (alumina) more likely to damage a Ti implant surface than glycine.…”
Section: Air Polishingmentioning
confidence: 99%
See 1 more Smart Citation
“…The hippocampus is a major part of the mesolimbic system, which mediates the effects of morphine. In addition, this system is involved in anxiety and fear (Biggio et al, 1990;Chairay et al, 1997;Deutch and Roth, 1990;Dunn and File, 1983; Fig. 4.…”
Section: Discussionmentioning
confidence: 99%
“…There is negative aspect of roughened surface Roughened surfaces produce a sheltering effect for bacterial adhesion protecting them from shearing forces, and allowing them the stability and time to easily transform their adhesion from a reversible bond to an irreversible bond onto the substrate 55. In addition, rough surfaces are capable of accumulating increased thickness/area IJBAR (2012) 03(10) www.ssjournals.com of plaque and number of colony forming units of bacteria. As time progresses with undisturbed matured plaque, rough surfaces tend to harbor more motile organisms and spirochetes 55 63 .This difference was possibly due to differences in duration of application, as Augthun's group only applied the air abrasive for 60 seconds. Besides altering implant surfaces, additional concerns such as possible retained particles after administration and application of compressed air intra-orally may raise some concerns toward this treatment modality.…”
Section: Colonization/plaque Maturationmentioning
confidence: 99%